Analisis Penerapan Akuntansi Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) dan Kegunaan Informasi Akuntansi - Siti Salma Sitio; Yenni Samri Juliati; Kusmilawaty Kusmilawaty (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research aims to find out whether accounting based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) has been implemented and whether the use of accounting information in Micro, Small and Medium Enterprises (UMKM) in Laut Dendang Village has been implemented. This research was conducted using qualitative methods with a descriptive approach. Data collection techniques in this research used observation, interview and documentation techniques. The types of data used are primary and secondary data as research data sources. The analysis technique used is data reduction, data presentation and drawing conclusions. Based on data analysis, the research results show that accounting based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) has not been applied to MSMEs in Laut Dendang Village. Even though MSME actors already have financial report records, the recording carried out is still simple and only in accordance with the understanding of each MSME actor. Several MSME players have also implemented the use of accounting information as evaluation material and consideration in making business decisions.